STUDENTS’ ATTITUDE IN LEARNING ISLAMIC EDUCATION COURSE THROUGH VALUES CHARACTER HABITUATION - Dede Imtihanudin; Ria Mariana (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2021)
The purpose of this study is to determine how character education can provide implications for student attitudes changing at the Islamic education learning at SDIT Widya Cendekia Serang. The population in this study were students of SDIT Widya Cendekia Serang at 6th year class. The technique of data collecting in this study are observation, interview, and documentation. The data used in this research are primary data, data collected directly by researchers by making direct observations and interviews with lecturer. The results of the study state that habituation in instilling character values ??can cause changes in students' attitudes in learning Islamic Education. Among the characters are: trustful, fond of good deeds, anticipatory, disciplined, hard working, responsible, sincere, honest, independent, and diligent.